Studies on the reproductive development of Leucospermum cv. Red Sunset with special reference to photoperiodic and hormonal control - Malan, D. G.(Daniel Gerhardus),1880-1937 (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. Agric.) -- University of Stellenbosch, 1993.